Newly synthesized G protein of vesicular stomatitis virus is not transported to the Golgi complex in mitotic cells. - Carol Featherstone; Gareth Griffiths; W. G. Warren (1985)
Newly synthesized G protein of vesicular stomatitis virus is not transported to the surface of cultured mammalian cells during mitosis (Warren et al., 1983, J. Cell Biol. 97:1623-1628). To determine where intracellular transport is inhibited, we have examined the post-translational modifications of G protein, which are indicators of specific compartments on the transport pathway. G protein in mitotic cells had only endo H-sensitive oligosaccharides containing seven or eight mannose residues, but no terminal glucose, and was not fatty acylated. These modifications were indicative of processing only by enzymes of the endoplasmic reticulum (ER). Quantitative immunocytochemistry was used as an independent method to confirm that transport of G protein out of the ER was inhibited. The density of G protein in the ER cisternae was 2.5 times greater than in infected G1 cells treated similarly. Incubation of infected mitotic cells with cycloheximide, which inhibits protein synthesis without affecting transport, did not result in a decrease in the density of G protein in the ER cisternae, demonstrating that G protein cannot be chased out of the ER. These results suggest that intracellular transport stops at or before the first vesicle-mediated step on the pathway.